WORK–FAMILY CONFLICT AND WORK ENVIRONMENT ON ORGANIZATIONAL COMMITMENT: MODERATING ROLE OF PERCEIVED ORGANIZATIONAL SUPPORT - Nur Afifah; Musdalifah Azis; Yana Ulfah (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Organizational commitment is essential in public sector organizations, especially among married employees managing both work and family responsibilities. This study examines the effects of work–family conflict and work environment on organizational commitment, with perceived organizational support as a moderating variable. Using a quantitative explanatory design, 46 married employees from a local government agency in Indonesia participated in the study. Data were collected through Likert-scale questionnaires and analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM). Findings indicate that work–family conflict negatively and significantly affects organizational commitment, while the work environment has a positive and significant effect. Perceived organizational support moderates both relationships, buffering the negative effect of work–family conflict and enhancing the positive impact of work environment. These results highlight the importance of organizational support as a contextual mechanism in sustaining commitment among married public sector employees. Practically, organizations should manage workloads, improve work conditions, and provide consistent support to maintain employee commitment. This study contributes to human resource management literature by demonstrating how perceived organizational support shapes the interplay between work–family conflict, work environment, and organizational commitment.